2013
DOI: 10.1117/12.2031250
|View full text |Cite
|
Sign up to set email alerts
|

CDOM retrieval using measurements of downwelling irradiance

Abstract: As it can strongly influence the availability of light and thus primary production, coloured dissolved organic matter (CDOM) affects the function of lake ecosystems. Therefore reliable methods are required for the monitoring of CDOM concentration. A new method using downwelling irradiance was tested for applicability in four selected lakes of the Bavarian Osterseen Lake District, which consists of 19 naturally connected freshwater lakes of different trophic level. The method separates between the direct and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…This is in accordance with previous studies which showed that, for accurate Chl-a concentration retrieval, a layer of water above the sensor of at least 1 m (depending on overall water constituent concentration ranges) was required [44,51]. a CDOM (440), compared to results from water analytics, showed a deviation of about 57% from PSICAM and 32% from LWCC measurements.…”
Section: Water Constituent Retrieval From Downwelling Irradiance Specsupporting
confidence: 77%
See 1 more Smart Citation
“…This is in accordance with previous studies which showed that, for accurate Chl-a concentration retrieval, a layer of water above the sensor of at least 1 m (depending on overall water constituent concentration ranges) was required [44,51]. a CDOM (440), compared to results from water analytics, showed a deviation of about 57% from PSICAM and 32% from LWCC measurements.…”
Section: Water Constituent Retrieval From Downwelling Irradiance Specsupporting
confidence: 77%
“…To the authors' best knowledge, this is the only model that can handle the high variability of E − d (λ, z) measurements induced by wave focusing. Inverse modeling allows the derivation of the sensor depth z, the concentration of phytoplankton and the absorption coefficient of CDOM if f dd and f ds are treated as fit parameters together with z, C Chla and a CDOM (440) [44,51].…”
Section: Downwelling Irradiance In Watermentioning
confidence: 99%
“…For lakes with chl-a and CDOM concentrations similar to Lake Starnberg, this critical depth is in the order of 1.0-1.5 m [71,72]. Following this principle, we estimated the CDOM parameters a CDOM (440) and S from RAMSES E d (z < 0, λ) measurements in water.…”
Section: Retrieval Of Inherent Optical Properties From In Situ Measurmentioning
confidence: 99%
“…The downwelling irradiance in water, ( < 0, ) , can be used for determining the concentration of phytoplankton [71] and CDOM [72] if sensor depth z is large enough to capture the impact of absorption by water constituents on the spectral signature of ( < 0, ). For lakes with chl-a and CDOM concentrations similar to Lake Starnberg, this critical depth is in the order of 1.0-1.5 m [71,72].…”
Section: Retrieval Of Inherent Optical Properties From In Situ Measurmentioning
confidence: 99%